2019
DOI: 10.2503/hortj.utd-085
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the <i>pat-2</i> Gene and Auxin Biosynthesis Inhibitor on Seed Production in Parthenocarpic Tomatoes (<i>Solanum lycopersicum</i> L.)

Abstract: In pat-2 parthenocarpic tomatoes (Solanum lycopersicum L.), inhibition of seed production prevents their breeding and development. Low seed set is thought to be caused by a pleiotropic effect of the pat-2 gene because the number of seeds from pat-2 parthenocarpic tomato cultivars is generally low; however, research on the relationship between low seed set and the pat-2 gene is lacking. In this study, to clarify the effect of the pat-2 gene on seed production and develop a method for promoting seed production i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…This study was in line with the research of Liu et al (2018) on SlARF5-6 parthenocarpic transgenic tomato, which showed a high AUX response, resulting in a lower number of seeds compared with the WT. According to Takisawa et al (2019) low seed production was attributed to two reasons, i.e. (1) formation of pseudo-embryo from the innermost layer of the embryo sac and (2) inhibition of pollen tube elongation.…”
Section: Discussionmentioning
confidence: 99%
“…This study was in line with the research of Liu et al (2018) on SlARF5-6 parthenocarpic transgenic tomato, which showed a high AUX response, resulting in a lower number of seeds compared with the WT. According to Takisawa et al (2019) low seed production was attributed to two reasons, i.e. (1) formation of pseudo-embryo from the innermost layer of the embryo sac and (2) inhibition of pollen tube elongation.…”
Section: Discussionmentioning
confidence: 99%
“…Parthenocarpy is a highly desirable agronomic trait, as fruit formation is less affected by environmental factors ( Molesini et al., 2020 ). Thus far, several parthenocarpic mutations, such as pat-2 , iaa9-3 , and pad-1 , display high seedless fruit set ratios, and hence, they are considered potential genetic materials for the breeding of seedless tomato fruit cultivars ( Takisawa et al., 2019 ; Matsuo et al., 2020 ; Takisawa et al., 2020 ; Tran et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%